The effects of Situational Interview (SI) and Patterned Behavior Description Interview (PBDI) on applicant reactions - Mahadi, Masyitah; Alias, Alizi; Ismail, Isma Suhaila (INSI Publications, 2015)

(untitled)
Using interview as one of the selection methods for recruitment, organizations not only aim to select the best candidates for the job but also want to attract them to work in their organizations. This suggests applicants‟ reactions to job interview do matter. Objective: This study sought to examine applicant reactions to different types of structured interview content by comparing between Situational Interview (SI) and Patterned Behavior Description Interview (PBDI). Method: Forty six job incumbents, as samples, were given transcripts of interview content for SI and PBDI which were counterbalanced in the order of their presentation. After completing them, the participants were asked to answer a short questionnaire on applicant reactions to the two types of structured interview content. Results: The results demonstrated a significant effect of structured interview content on applicants‟ fairness or procedural justice perception, with the mean for PBDI is significantly greater than the mean for SI. Conclusion: The findings showed that using interview transcript, job incumbents reacted more positively to PBDI than SI, which indicated that participants regarded PBDI to have a higher perceived procedural justice or perceived fairness than SI. These findings have contributed better understanding to the contradicting findings in earlier empirical researches